Case Study Pembelajaran IPS Terpadu Peningkatan Pemahaman Siswa terhadap Iklim di Indonesia SMP Negeri 4 Jerowaru Lombok Timur - Ahmad Turmuzi (Journal on Education, 2022)
The integrated IPS equation with basic IPS is one of the differences in subjects at school. Several schools make social studies subjects to increase understanding of the social environment, nature and circumstances surrounding the climate. There is a difference in teaching in the integrated IPS family with basic IPS from the learning methods and achievement of the subjects taught by teachers in different schools. There are some students who cannot understand social studies learning at the junior high school level. The purpose of this study is to provide social studies teaching equations in an effective and efficient way with the hope that students are able to take part in classical learning in social science classes with high cognitive aspects. The research methodology uses a descriptive qualitative approach. Case study research design on 2 class VII students as the main informants and 1 social studies teacher class VII as a supporter. The results of the study describe that increasing students' understanding of climate conditions in Indonesia by introducing online maps and globes or Google maps provides the latest and easiest way to understand lessons in the social field broadly. There is no limitation of students in studying social sciences. Freedom in understanding the type of social science learning is the key to the success of innovative methods to achieve student indicators in classroom learning.